Business due diligence and Human Rights: Towards a Spanish Law - Fernández Liesa, Carlos R. (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
An analysis is made of the new context of companies in the protection of human rights and the environment, which has led to the need to progressively develop international, european and national law. To this end, it is necessary to overcome the current state of voluntariness and move from soft law to hard law also through the elaboration of national laws. The analysis of comparative law models and international standards are addressed. The main elements of the due diligence of the State and of the companies are deepened as well as the main questions that a law of this nature raises.
Keywords: Due diligence; Comparative business law and human rights; Standars of international organizations; Business and human rights